Labrador Sea Water Formation Rate and Its Impact on the Local Meridional Overturning Circulation. Issue 8 (13th August 2019) - Feucher, Charlène; Garcia‐Quintana, Yarisbel; Yashayaev, Igor; Hu, Xianmin; Myers, Paul G.
Abstract: This paper investigates the link between the Labrador Sea Water (LSW) formation rate and the strength of the Atlantic Meridional Overturning Circulation within the Labrador Sea. LSW is formed in the Labrador Sea through deep wintertime ocean convection and is then carried out of the basin by, among other currents, the Deep Western Boundary Current (DWBC) that flows southward along the east coast of Canada. We used an eddy‐permitting simulation (at 1/12°, horizontal resolution) with an Arctic and Northern Hemisphere Atlantic configuration of the Nucleus for European Modeling of the Ocean (NEMO) model that covers the period from 2002 to 2017. In this study, the formation rate of LSW is estimated using an instantaneous kinematic subduction approach by analyzing the vertical transport of a water mass through the base of the mixed layer. We computed the local Meridional Overturning Circulation (MOC) index and the transport of LSW within the DWBC at the Atlantic Repeat hydrographic section 7 West (AR7W). Results show that an increase in the formation rate of LSW entails an increase in the LSW transport in the DWBC within 1 year. This is followed by an enhancement of the overturning in the Labrador Sea. Plain Language Summary: The Atlantic Meridional Overturning Circulation (AMOC) is of paramount importance for the climate. The AMOC contributes to the redistribution of heat, salt, and anthropogenic carbon in the world's oceans. The upper limb of the AMOC transports warm, surface water northward. The lower limb of the AMOC is associated with dense, cold, and deep water formation and is carried by a vigorous Deep Western Boundary Current (DWBC). The Labrador Sea Water (LSW) is one of the water masses formed by deep convection in the subpolar gyre and then carried out of the basin by, among other currents, the DWBC that flows southward along the east coast of Canada. In this paper, we use a simulation to investigate how the change in the formation rate of the LSW could impact the strength of the local AMOC in the Labrador Sea. We found that an increase in the formation rate of LSW entails an increase in the LSW transport in the DWBC within 1 year. This is followed by an enhancement of the overturning in the Labrador Sea. Key Points: Strong convection events in the Labrador Sea entail a high formation rate of Labrador Sea Water Part of the Labrador Sea Water is exported out of its formation region through the Deep Western Boundary Current within 1 year Strong, deep convection events are related to a higher local MOC index in the Labrador Sea along the AR7W section